Electrocochleography in the diagnosis of third window conditions - Paul R. Kileny; Megan M. Cherry; Devin L. McCaslin (Frontiers in Neurology, 2024)
IntroductionSuperior semicircular canal dehiscence (SSCD) is the best-known and most common presentation of so-called “third window conditions.” There are a variety of diagnostic measures and tests for this condition in the current literature, including air-bone gap, vestibular-evoked myogenic potentials, and electrocochleography (EcochG). The purpose of this study was to investigate the diagnostic utility of EcochG and its relationship to air-bone gap in a cohort of patients with confirmed SSCD.MethodsWe reviewed data from 20 patients (11 female and 9 male subjects, age ranging 21–78 years), with confirmed unilateral or bilateral superior canal dehiscence. In total, 11 patients had unilateral SSCD and 9 patients had bilateral SSCD as determined by high-resolution CT scan. This resulted in the inclusion of twenty-nine ears with superior canal dehiscence and 11 normal ears.ResultsOur results indicated that all confirmed SSCD ears presented with an abnormal EcochG SP/AP value and that there was a statistically significant difference between normal and dehiscent ears. There was no statistically significant relationship between air-bone gap and SP/AP ratio in the ears diagnosed with SSCD nor was there a significant difference between dehiscent and normal ears in terms of air-bone gap at three frequencies.DiscussionThese results are consistent with previous studies showing the diagnostic utility of EcochG for this condition and the variability of air-bone gap. While an unexpected air-bone gap continues to be a red flag for SSCD, its absence along with the presence of subjective symptoms is a reasonable indicator for further clinical investigation to include EcochG.